A higher order thermoelastic analysis of fatigue crack growth can assess crack tip shielding. Issue 4 (30th January 2023) - Camacho‐Reyes, Alonso; Vasco‐Olmo, Jose M.; James, M. Neil; Diaz, Francisco A.
Abstract: The present work uses a more accurate thermoelastic formulation than the classical equation, based on the inclusion of a higher order term, to analyze crack tip thermoelastic data. It is shown that this thermoelastic analysis (TSA) model can be fitted to the Christopher–James–Patterson crack tip field model and hence provides information on crack tip shielding. To validate the results of this analysis, stress intensity factors (SIFs) were compared with results obtained from digital image correlation (also fitted to the CJP model). A comparison was also made between these CJP‐derived SIF values and those obtained using a purely elastic Irwin–Westergaard approach. A high level of agreement was observed between DIC and TSA results in assessing ΔKCJP that is the net result of the driving and the shielding forces on the crack tip. The ability to assess shielding using TSA is a significant step forward in its potential use in a more accurate characterization of crack tip fields. Highlights: A high‐order thermoelastic formulation is used to evaluate the crack shielding phenomenon. CJP model experimental implementation using crack tip thermoelastic data. High level of agreement between TSA and DIC results in terms of Δ K CJP .